2004
DOI: 10.1111/j.1532-5415.2004.52492.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Predictors of Pneumonia in Elderly Patients: Importance of Functional Assessment

Abstract: Functional status was an independent predictor for short- and long-term mortality in hospitalized patients whereas CAP severity predicted functional decline. Severity indices for CAP should possibly thus be adjusted in the elderly population, taking functional status assessment into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
136
1
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(156 citation statements)
references
References 24 publications
16
136
1
3
Order By: Relevance
“…21 Viral infection in nursing homes is seasonal. 22,23 In the present study, we also found seasonality of the H1N1 epidemic in NHAP cases, particularly in region II (39% vs 13%, P ϭ .16).…”
Section: Etiologysupporting
confidence: 59%
“…21 Viral infection in nursing homes is seasonal. 22,23 In the present study, we also found seasonality of the H1N1 epidemic in NHAP cases, particularly in region II (39% vs 13%, P ϭ .16).…”
Section: Etiologysupporting
confidence: 59%
“…Such flexibility is widely validated in similar settings. [33][34][35][36] It also appears to us to be analogous to the advanced computing techniques that we have used in recent inquiries to enhance the performance of the high-dimension Frailty Index. 15,37 For instance, an artificial neural network can be used to calculate weighted scores, and can significantly improve the Frailty Index's predictive performance over an unweighted version.…”
Section: Discussionmentioning
confidence: 99%
“…Nosocomial pneumonia remains one of the major causes of morbidity and mortality. 1,2 Re-evaluation at 72 h after treatment is crucial to detect treatment failure as well as to prevent other complications. 3,4 Unfortunately, traditional parameters fail to assess the clinical efficacy at an earlier stage.…”
Section: Introductionmentioning
confidence: 99%